A TOXIC LEGACY OF ENDOSULPHAN: TRACING TRAUMA IN THE NOVEL SWARGA BY AMBIKASUTHAN MANGAD - Nair, Reena (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Ever since the existence of human beings, various forms of atrocities like wars, terrorist activities, communal skirmishes, natural calamities, sexual offences, etc. have been occurring paying the price for mental and physical beings. The scars caused by violence have a resonating impact on humans leaving a profound psychological imprint in the human mind causing trauma. Trauma has emerged as a keyword to approach violence and its aftermath thus gaining impetus in the critical and literary realm. It is quite appalling to note that human beings themselves pose a great peril to the sustenance of their fellow beings. In a world driven by materialistic concerns, the humane aspect is deplorably nonexistent from all walks of life. Globalisation has alarmingly set its pace exploiting all resources on our earth making it an uninhabitable place. In a scenario, where the capitalists are enthralled with the absolute mantra of reaping maximum profit from minimal effort, the perpetrators of disequilibrium are numerous. Many hazards are bound to occur as a result of the connivance of the state officials with international organisations causing umpteen problems to fester leading to gruesome traumatic experiences among the ordinary folk. The trauma caused by endosulfan, a lethal pesticide, is one such catastrophic disaster that affected a major population in Kasargode in Kerala. Though the initial phase of spraying endosulfan seemed innocuous to the naive populace, it had a gruesome impact on those hapless people. This incident had its repercussions globally leading to the complete banning of endosulfan. The literary realm could not unlink itself from the dismal happenings affecting the innocent society and many activists from the literary domain including Sugathakumari, Leelakumariamma, Ambikasuthan Mangad, etc. had taken a keen interest in erasing the panic among the victims and restoring resilience among them. The express purpose of the present paper is to delve deeper into the myriad ways in which endosulfan victims are yet traumatised both physically and mentally by undertaking a critical expedition through trauma theories. The gruelling event though was not assimilated at the time of its occurrence has great relevance in the current context as it demands sensible reactions and interventions from the academic circle rendering meaning to human lives.